Chapter Dall'intuizione all'immersione: architettura e neuroscienze - Farling, Melissa (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
Argues that architect's have a moral imperative to transform and support living conditions and recommends a hippocratic oath for architects to recognise their responsibility to support human wellbeing. A value change needs to shift from considering architecture as an object to architecture as experience and architectural education must take the lead. Discusses the importance of empathy and defining performance outcomes. Suggest ways to apply neuroscientific research at multiple scales